Perceptions about user intake in primary care in the city of Rio de Janeiro - da Silva, Tarciso Feijó; Romano, Valéria Ferreira (Journal of Health Care, 2016)
Introduction: This article covers issues involving user intake in primary care in the city of Rio de Janeiro, Brazil. Objective: To examine the practice of professionals from two primary care units in that city and present weaknesses perceived and referred by these professionals regarding the operationalization of the intake. Methods: The research was developed through systematic observation techniques and semi-structured interviews, and it was analyzed considering the references of Content Analysis supported by Bardin. Results: Problems in the construction of the response capacity of professionals were found, as well as difficulties in the relational integration between professionals of the Family Health Strategy and Family Health Support Center, reflecting in problems in the conduction of the coordination of care. Conclusion: The recognition of those weaknesses, in the prospect of boosting reflections and actions, scale the expectation that primary care in the city of Rio de Janeiro may be constituted in the construction of coping parameters on their work process, seeking strategies of institutional support, of the staff, and of users to manage the intake.